Development of Natural Materials Gondorukem with Petroleum Ether, Anchor with Water as Fossil Conservation Materials - Anindhita, Rizky; Harismah, Kun (Prosiding University Research Colloquium, 2021)
Fossil conservation is one form of efforts to preserve fossils through the maintenance and preservation of fossils. The fossil conservation method commonly used by the Sangiran Early Man Site Preservation Center is the rock conservation method. If a fossil is found that is broken or cracked, it is necessary to attach it using an epoxy resin type adhesive. In this study, the experiment that will be carried out aims to provide an alternative adhesive material from natural materials used for joining fossils and to compare the effectiveness of natural adhesives with existing adhesives, namely epoxy resin. Natural materials Anchor and Gondorukem (Resina colophonium) have been used as conservation materials in Sangiran. Petroleum has never been processed into a conservative solvent for fossil conservation. Therefore, this study chose a petroleum solution to be used as a solvent for the conversion material used to conserve fossils. The way to make adhesive from natural materials using petroleum solution is to grind the natural ingredients into powder, which is then dissolved in petroleum solvent before being applied to fossils.